2012
DOI: 10.1007/s10103-012-1083-6
|View full text |Cite
|
Sign up to set email alerts
|

Topical photodynamic treatment with poly-l-lysine–chlorin p6 conjugate improves wound healing by reducing hyperinflammatory response in Pseudomonas aeruginosa-infected wounds of mice

Abstract: We report the results of our investigations on the effect of antimicrobial photodynamic treatment (APDT) with poly-lysine-conjugated chlorin p6 (pl-cp6) on proinflammatory cytokine expression and wound healing in a murine excisional wound model infected with Pseudomonas aeruginosa. Treatment of infected wounds with pl-cp6 and light doses of 60 and 120 J/cm(2) reduced the bacterial load by ~1.5 and 2.0 log, respectively, after 24 h. The treated wounds healed ~5 days earlier as compared to untreated control and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
65
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 36 publications
4
65
0
1
Order By: Relevance
“…Another recent clinical study reported that APDT of P. aeruginosa-caused skin ulcers in the lower limbs resulted in significant bactericidal outcome and wound healing-promoting effects [232]. This is in line with a previous study in mice, where APDT was shown to reduce the hyper-inflammatory response in P. aeruginosa-infected skin wounds [233]. Additionally, APDT is also used in the clinical management of diabetic foot, which causes sizeable infection-related complications in diabetic patients.…”
Section: In Vivo and Clinical Status Quo Of Antibacterial Photodynamisupporting
confidence: 78%
“…Another recent clinical study reported that APDT of P. aeruginosa-caused skin ulcers in the lower limbs resulted in significant bactericidal outcome and wound healing-promoting effects [232]. This is in line with a previous study in mice, where APDT was shown to reduce the hyper-inflammatory response in P. aeruginosa-infected skin wounds [233]. Additionally, APDT is also used in the clinical management of diabetic foot, which causes sizeable infection-related complications in diabetic patients.…”
Section: In Vivo and Clinical Status Quo Of Antibacterial Photodynamisupporting
confidence: 78%
“…Mills [18] proved MAL-PDT increases MMP-1, MMP-9 and TGF-b3 production during matrix remodelling, ultimately producing scars with improved dermal matrix architecture. Sahu's study [25] showed that photodynamic treatment of wounds with pl-cp6 not only kills the bacteria but also reduces hyper-inflammatory response of P. aeruginosa-infected wounds in mice, leading to acceleration of wound healing. Currently, however, no basic research has fully elucidated related mechanisms, which still await further in-depth studies.…”
Section: Discussionmentioning
confidence: 98%
“…e The skin ulcer surface was significantly cleaner and the size was reduced 3 days after the second PDT treatment Arch Dermatol Res anti-inflammatory, and healing-promoting effects [1]. Fourth, Several novel studies have demonstrated that PDT has positive effects on histological aspects of wound healing [18,23,25]. Mills [18] proved MAL-PDT increases MMP-1, MMP-9 and TGF-b3 production during matrix remodelling, ultimately producing scars with improved dermal matrix architecture.…”
Section: Discussionmentioning
confidence: 98%
“…PDT, in addition to the antibacterial effect, has also been shown to have influence on several other factors like bacterial toxins [4], proinflammatory cytokines [5], matrix metalloproteases, collagen synthesis, and remodeling [6] in wounds. Therefore, APDT appears promising for the treatment of diabetic wounds where healing is impaired and the treatment is further complicated by bacterial infection [7][8][9].…”
Section: Introductionmentioning
confidence: 98%